Approaches to the definition of internal financial control - D. R. Khabibullina (Путеводитель предпринимателя)
The article presents an analytical review of Russian and foreign approaches to understanding internal financial control. Different opinions of economists on the methods and tasks of internal financial control have been studied. As the main trend of the study of internal financial control, the strengthening of the role of the system approach is called. The article examines the main domestic models of internal control (indicative, effective, risk-oriented) and provides a comparative analysis of international models of internal control (COSO, COBIT, Ternbull Rewiev Group, KonTraG). The article concluded that it is necessary to increase the effectiveness of the internal control system through a risk-based model. The analysis of approaches to understanding this concept allowed to form a theoretical basis for studying the issues of practical formation of the internal control system.